When we went first class - Williamson, Ellen (Doubleday & Co. Garden City, New York, 1977)
The author recalls the lifestyle she shared with the rich and powerful in the 1920's, 30's, and 40's--a comfortable life with homes in several places and leisurely travel by ocean liner or Pullman car.
San Francisco; Scotland in Iowa; Motoring; Lower and higher learning; Traveling by rail; Santa Barbara Winters; Traveling by ship; Gangsters and Debutantes; Keeping clean and cool; Aviation; Cafe society; City Hall; War, Work, and play; Tea in Tigertown; Still traveling
Keywords: Ellen Williamson -- 1905-; Social life and customs -- Description and travel; United States -- Social life and customs -- 1918-1945